Assessing the Total Cases of Shoplifting in Barangay 171 Bagumbong, Caloocan City During the Pandemic: Vol.3, No.1C (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This study aims to determine the differences between superandi and modus of shoplifters. In Barangay 171, Bagumbong Caloocan City, there are many shoplifting incidents in different stores based on their records, but only a few incidences were reported at Bagumbong Police Station. Other stores choose not to report it, but instead of the security personnel already catching the shoplifters in the act, they refer them to the management and usually require them to pay what they stole eight times—shoplifting steal from all types of stores, including department stores, speciality shops, supermarket, drug stores, discounters, music stores, convenience stores, thrift shops, large companies, and small mom and pop shops. Shoplifting can hurt more than just the business from which you are stealing. It causes a tidal wave of other problems that are not apparent on the surface. (Studymoose, n.d.) The researcher used a descriptive method to determine the total shoplifting cases in Barangay 171, Bagumbong Caloocan City. Descriptive research may be defined as purposive processes of gathering, analyzing, and classifying data about conditions process and cause-effect and relationship, making them accurate data with or without statistical methods. The researchers conducted a survey and interviewed the respondents. The instruments used by the researchers for this research all have a significant purpose for the researchers to achieve enough information needed for the study. The study concluded that based on the demographic profile of the respondents. On the part of barangay officials, it is 50 and above years old with a frequency of 2 or 66.7 %.On the part of store employees aged mostly 18-25 years old with a frequency of 5 or a percentage of 71.4%, on assessing the total number of shopliftings in Barangay 171, Bagumbong Caloocan City during the pandemic in terms of security personnel, course of action, and security management were regarded as “highly capable,” on problems encountered by the respondents assessing the total number of shopliftings in Barangay 171, Bagumbong Caloocan City during the pandemic were regarded as “serious” and on the measures proposed to solve the problems encountered were regarded as “Highly recommended.” The study's findings showed the assessment of total shoplifting cases in Barangay 171 Caloocan City. The security personnel was highly recommended, and the action was considered capable. However, the researchers came up with recommendations such as providing safety tools like working CCTV and ground mirrors. Conduct patrols, search, rescue, and recovery operations must coordinate with other security providers such as Barangay Police, Philippine National Police, and other service providers. Follow the efficient recruitment and selection system of qualified personnel and develop a program that will encourage and help security personnel keep up new learning and skills in a row with the continuing security techniques and procedures.